Dynamic Approval Matrix Application Design for Technical Department Document Change Request Application - Riska Zulfiqoh; Muhamad Bahrul Ulum (JURNAL TEKNIK INFORMATIKA, 2022)
This study discusses problems on the website of the NPPS companywhich will also be used by its branch company, namely NPPSLK.While the website currently only supports one company, it isnecessary to develop the website to become multicompany. If thewebsite is made multicompany, then the applications in it areautomatically adjusted. One of the applications on the website is anapplication with systematic approval, namely the Dynamic ApprovalMatrix (DAM). DAM was developed to be able to supportmulticompany, support flow management features, status, andapproval actions for each company. So, a multi-company configuration is carried out on one system, and using the waterfall method with steps. Advance Dynamic ApprovalMatrix (ADAM) was created as multi-enterprise support DAMdevelopment. So, it can be used by multi-company. ADAM is madeusing waterfall method using Odoo with Python, XML, andPostgreSQL. The app contains forms to manage related apps, approvalflow settings, multi-company, status settings, and Call-to-Actionbuttons to facilitate document approval. The ADAM application has been tested on the TDCR application using black box indicator with the conclusion that website results aremore effective and efficient because it can be used by multicompany,and administrators can freely adjust according to company needs.